Comparative studies on germination and seedling growth of on-season and off-season produced jute seeds - Islam, Rashidul; Fakir, Md Solaiman Ali; Hossain, M Abul (Fundamental and Applied Agriculture, 2019)
To overcome the problems of crop loss and prolonged period of land engaged for jute seed production in on-season, the off-season production of jute seeds is being practiced but the seed quality of both these systems has not been thoroughly compared to get better seeds for higher yield in jute. Considering the above facts, the present research was carried out to perform a comparative study among different parameters, such as, germination and seedling growth of on-season and off-season produced seeds of Corchorus capsularis (Variety CVL-1) and Corchorus olitorius (Variety O-9897). In this study, significant influence of production period of seeds on germination percentage, seedling vigor index, germination co-efficient, shoot length, root length, shoot and root dry weight, ratio of root dry weight and shoot dry weight was observed. The highest seed germination percentage, seed germination co-efficient, seedling vigor index, shoot and root length, shoot and root dry weight, ratio of root dry weight and shoot dry weight were found in off-season Deshi jute seeds followed by on-season Deshi and off-season Tossa jute seeds. The lowest value of each of these properties was found in case of on-season Tossa jute seeds and seedlings. Based on the findings of this study, it may be concluded that off-season produced jute seeds showed better performance than those of on-season jute seeds in both the species in terms of seed germination and other relevant characters.